Seasonal space use and habitat selection in magpie geese: implications for reducing human‐wildlife conflicts. Issue 7 (5th July 2022) - Corriveau, Amélie; Klaassen, Marcel; Garnett, Stephen T.; Kaestli, Mirjam; Christian, Keith; Crewe, Tara L.; Loewensteiner, David A.; Campbell, Hamish A.
Abstract: Negative interactions between waterbirds and people are increasing. Waterbirds feeding on agricultural crops cause significant losses to farmers worldwide, but so far most research to address these conflicts has been conducted on migratory species in the temperate northern hemisphere. We investigated the space use and habitat selection of the magpie goose ( Anseranas semipalmata ), a taxonomically distinct waterbird endemic to Australia and southern Papua New Guinea. In tropical northern Australia, magpie geese are protected but are increasingly persecuted by farmers to protect crops during the late dry–early wet season (~Sep–Jan), a bottleneck of natural resources for waterbirds in the monsoonal tropics. Using satellite telemetry of 38 geese spread across 3 seasons (2016–2017, 2017–2018, 2018–2019), we evaluated daily and seasonal space use, individual site fidelity, and habitat selection to determine the extent of use of agricultural fields by geese, and the spatiotemporal scales at which management should be undertaken. Geese used relatively small daily areas ( x̄  = 8.2 km 2 ) consistently throughout the late dry–early wet season, and repeatedly used agricultural fields, forested bushlands, and local wetlands. Geese used comparatively large seasonal areas ( x̄  = 219.5 km 2 ) encompassing several agricultural areas, and had a low mean overlap between successive weekly core activity areas, indicating that site fidelity rapidly weakened over time. These results suggest that farm‐scale (<30 ha) management of geese is unlikely to be effective because hazed individuals are likely to be replaced soon afterwards. Instead, our findings suggest that goose management should be coordinated strategically at the local (~1, 000 ha), or regional (~100, 000 ha) scale. Farm‐level management would likely be more effective if implemented in conjunction with the creation of regional sanctuaries where geese could rest and potentially feed undisturbed away from farms. Our findings can be used by wildlife managers for optimizing the location of such sanctuaries and highlight the necessity for management to be adaptive given the opportunistic nature of the species. Abstract : We investigated the space use and habitat selection of tropical magpie geese to determine the extent of use of agricultural fields and to evaluate appropriate spatiotemporal scales for management. Geese used space opportunistically and preferentially selected irrigated agricultural fields over other land cover types, highlighting that management efforts will benefit from being adaptive, coordinated at the regional scale, and implemented in conjunction with the creation of disturbance‐free sanctuaries for geese.